2005
DOI: 10.1038/sj.cgt.7700801
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cells as cellular vehicles to deliver gene therapies to metastatic tumors

Abstract: A long-pursued goal in cancer treatment is to deliver a therapy specifically to metastases. As a result of the disseminated nature of the metastatic disease, carrying the therapeutic agent to the sites of tumor growth represents a major step for success. We hypothesized that tumor cells injected intravenously (i.v.) into an animal with metastases would respond to many of the factors driving the metastatic process, and would target metastases. Using a model of spontaneous metastases, we report here that i.v. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 18 publications
0
49
0
1
Order By: Relevance
“…This cassette was placed directly downstream of the fiber gene, as an L6 unit ( Figure 1a). This strategy has been used previously 7,19 and cloning strategies are available upon request. Transfection of the AdwtRGD-GALV genome into 293 cells led to massive syncytia formation ( Figure 1b) and virus generation.…”
mentioning
confidence: 99%
“…This cassette was placed directly downstream of the fiber gene, as an L6 unit ( Figure 1a). This strategy has been used previously 7,19 and cloning strategies are available upon request. Transfection of the AdwtRGD-GALV genome into 293 cells led to massive syncytia formation ( Figure 1b) and virus generation.…”
mentioning
confidence: 99%
“…We have previously demonstrated that tumor cells can be used to target tumors. 19 OCCAV-infected D17 carrier cells displayed a much more effective antitumoral effect as compared with Abrams carrier cells in systemic injections, probably because of a higher viral burst of D17 cells (Figure 1a, panel A) than of Abrams cells (Figure 1a, panel B), which offers increased potential for dose amplification. Moreover, further confirmation that viral production in carrier cells is linked to antitumoral activity comes from the observation that the homogeneous mix of infected cells showed an intermediate therapeutic efficacy between the D17 and Abrams-infected carrier cells.…”
Section: Discussionmentioning
confidence: 99%
“…injected tumor cells homed in metastatic lesions and were able to deliver OVs to the metastases with only localized and negligible systemic toxicity. 18,19 Moreover, in an immunocompetent model, tumor carrier cells loaded with adenovirus generated anti-adenovirus and antitumoral cytotoxic T-lymphocytes, the activity of which could be further enhanced by granulocyte-macrophage colony-stimulating factor expression. 10 In this study, we explored the potential of using canine tumor cells as carriers for delivery of oncolytic canine adenovirus to tumor sites in a xenograft animal model.…”
Section: Introductionmentioning
confidence: 99%
“…An assortment of cells have been explored in this regard, including tumor cells, [49][50][51][52] outgrowth endothelial cells, 53 mesenchymal progenitor cells, 54,55 T cells 56,57 and monocytes. 58 There are several criteria that need to be addressed when determining which cell type should be utilized as a carrier for the delivery of a given oncolytic virus: (i) susceptibility to oncolytic virus infection, (ii) protection of the cargo from antibody neutralization, (iii) homing to sites of tumor growth and (iv) transfer of virus progeny to tumor tissue.…”
Section: Utilization Of Cell Carriers To Circumvent Virotherapy Barriersmentioning
confidence: 99%
“…Briefly, irradiated and non-irradiated cells were infected with VSV-GFP (MOI ¼ 0.5, 1 and 5) as described previously. At 48 h after infection, culture supernatants from infected cells were collected and virus titers were determined on Vero cells using TCID 50 titration method. As depicted in Figure 3e, cells exposed to 40 Gy were still able to produce significant amounts of VSV-GFP, although there was a slight decrease in progeny virus production compared to non-irradiated cells.…”
Section: Cell Carriers To Deliver Oncolytic Virusesmentioning
confidence: 99%